2011
DOI: 10.1016/j.jtcvs.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Is off-pump coronary artery bypass grafting superior to conventional bypass in octogenarians?

Abstract: Objective Selected patients appear to benefit from off-pump coronary artery bypass compared with conventional coronary artery bypass with cardiopulmonary bypass. It is unknown whether elderly patients undergoing isolated coronary artery bypass grafting operations derive any benefit when performed off-pump. We hypothesized that off-pump coronary bypass offers a greater operative benefit to elderly patients when compared with conventional coronary artery bypass. Methods A total of 1993 elderly patients (age ≥8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 22 publications
1
34
0
2
Order By: Relevance
“…LePar et al found that OPCAB and CABG had similar rates of operative mortality (OPCAB 5.9% versus CABG 5.1%; p = 0.53), but a significant reduction in major complications (OPCAB 15.6%, CABG 20.1%; p = 0.04). There was a higher rate of peri-operative myocardial infarction in the OPCAB group (OPCAB 1.2% versus CABG 0.3%, p = 0.003) [19].…”
Section: Elderly Patientsmentioning
confidence: 90%
“…LePar et al found that OPCAB and CABG had similar rates of operative mortality (OPCAB 5.9% versus CABG 5.1%; p = 0.53), but a significant reduction in major complications (OPCAB 15.6%, CABG 20.1%; p = 0.04). There was a higher rate of peri-operative myocardial infarction in the OPCAB group (OPCAB 1.2% versus CABG 0.3%, p = 0.003) [19].…”
Section: Elderly Patientsmentioning
confidence: 90%
“…One recently published meta-analysis of 43 randomized clinical trials has shown no significant difference between CABG and OPCAB in the incidence of stroke and perioperative myocardial infarction but the incidence of postoperative AF was significantly reduced in the OPCAB group [16]. Another large multicentre trial that compared the safety of CABG and OPCAB in octogenarians showed a reduced risk of AF in patients operated without CPB [17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite encouraging early reports, results have varied [21,22]. LaPar et al [23] KEY POINTS Morbidity and mortality for CABG surgery in octogenarians is continuing to decrease.…”
Section: Surgical Mortalitymentioning
confidence: 99%
“…They found there was no difference in mortality or stroke. Likewise, LaPar et al [23] reviewed the outcomes of 1993 CABG patients aged at least 80 in a statewide database encompassing 16 different centers. They found that on-pump patients required more blood transfusion and had more prolonged ventilation and atrial fibrillation.…”
Section: Surgical Morbiditymentioning
confidence: 99%